On the some connections of fibre spaces - Bliznikas, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. И. Близникас. О некоторых связностях расслоенных пространств V. Bliznikas. Apie kai kuriuos išsluoksniuotų erdvių sąryšius